THE PHILOSOPHY OF WORK OF THE LUMADS1 IN SURIGAO DEL SUR, PHILIPPINES, AS AN ALTERNATIVE TO MODERN TECHNOLOGY AND GLOBALIZATION - Cutillas, Anesito L; Ocay, Jeffry V; Alburo, Hemres M; Montero-Ambray, Raymond (Journal of Agriculture and Technology Management, 2024)
This paper aims to contribute to addressing some of the recent social problems in the Philippines that globalization engenders through an engagement with the Surigao Lumads’ view of work as an alternative to globalization. In particular, this paper examines the impact of modern technology very briefly as an agent of globalization on some of the Lumad communities in Surigao and explores some of the ways in which they draw on their rich cultural heritage to confront and resist such global concerns facing them today. This is premised on the idea that the model of work by these local people can be an alternative to the destructive tendency of modern technology and globalization. The researchers argue that the local communities in the periphery (in this case the Lumads in Surigao) continue to view work as means for the satisfaction of needs and, therefore, the championing of this philosophy of work would contribute greatly to cushioning, if not preventing, the inevitable impact of globalization.